Vocathon - the usefulness of board games in vocabulary learning through the multiple intelligences approach / Lilly Metom ... [et al.] - Metom, Lilly; Alfred Tom, Amelia; Joe, Saira; Rozaimie, Awang (Universiti Teknologi MARA Cawangan Sarawak, 2019)
This paper presents a survey study of an innovation project, titled 'VOCATHON'. It is a language board game that is specifically designed for learning vocabulary at the tertiary level by adapting the psychological basis of Multiple Intelligences Theory by Howard Gardner. Past research has identified that learners' predominant intelligences are significant predictors for language learning that can be manipulated to motivate acquisition and obtain effective outcomes. Vocabulary learning is a crucial process of language acquisition, in which it engages learners' knowledge of word definitions, word formation, collocation, synonyms, and etc. This innovation project comprises a set of board game, which includes lexicons from two fields of discipline, namely, Social Sciences and Science and Technology. This project focuses on the employment of providing the learners with vocabulary items that reflect their multiple intelligences. For this purpose, this study aims to identify the diploma students' acceptance and feedback of the board game by employing the survey method towards the learning of vocabulary through the use of VOCATHON. Based on the survey conducted after playing the board game, the majority of the participants gave positive responses. VOCATHON is asserted to be an effective and practical language board game because it is able to manipulate learners' multiple intelligences as a learning strategy for enhancing their vocabulary skills and motivating their interest in the learning process. By adapting the right approach, it is important to guide students with diverse multiple intelligences in acquiring vocabulary in order to make language learning more effective and fun.